Corruption and its relation to prevalence and death due to noncommunicable diseases and risk factors: a global perspective - Felipe Botero-Rodríguez; Camila Pantoja-Ruiz; Diego Rosselli (Pan American Health Organization, 2022)
Objective. To describe the relation between corruption indicators and statistics on noncommunicable diseases and their risk factors by continent. Methods. An ecological study was conducted to examine the relation of the GINI coefficient, the Country Policy and Institutional Assessment (CPIA), and the Corruption Perception Index (CPI) with noncommunicable diseases, using the Spearmans rank correlation test. Results. There is a moderate and positive correlation between Corruption Perception Index and cause of death due to noncommunicable diseases and risk factors for these diseases (r = 0.532), prevalence of schizophrenia (r = 0.526), bipolar disorder (r = 0.520), and eating disorders (r = 0.677). There is a moderate negative association between the GINI index and cause of death due to noncommunicable diseases (r = 0.571) and smoking prevalence (r = 0.502), and between the Corruption Perception Index and mortality caused by cardiovascular diseases, cancer, diabetes, or chronic respiratory diseases between the exact ages of 30 and 70 years (r = 0.577) and malnutrition prevalence (r = 0.602). Conclusions. This study indicates a correlation between corruption and noncommunicable diseases and their risk factors. This suggests that the high prevalence of noncommunicable diseases and risk factors could be related with political practices that negatively impact the population. Further research should study the weight of these associations, to take action on the way corruption is impacting on the health of societies.